A design of experiments approach to optimise tensile and notched bending properties of fused deposition modelling parts. (August 2016) - Griffiths, Chrisian A; Howarth, Jack; De Almeida-Rowbotham, Gabriela; Rees, Andrew
As additive manufacturing expands from rapid prototyping into rapid production, it is becoming more important to consider the mechanical performance of candidate products in addition to their functional attributes as a prototype. This study demonstrates how a design of experiments approach can be used to optimise the tensile and notched bending properties of the materials used in the process, while also considering the time of production and material efficiency. Such an approach can allow manufacturers to optimise the build in terms of the time, cost and material properties according to the requirements of the product. The main conclusion of this study was that when considering the significant contributors, similar build parameters result in optimised properties for both specimen types. It was also found that the layer height, being insignificant to the mechanical properties of both specimens, was critical to the cost control in terms of build time and material usage. Thus, the maximum layer height could be used to incorporate cost control into the design without affecting final performance.